STRUCTURES AND PATHS FOR THE EXPLORATION OF LANDSCAPE – CULTURAL MOSAIC - Taverna, Mario; Piccinini, Livio C.; Chang, Ting Fa Margherita; Iseppi, Luca (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The main aim of this paper is to highlight the evolution of urban and peri-urban networks in view of their use by dwellers and visitors. It considers the knowledge as a part of a hidden permanent education form, and as a prerequisite for full enjoyment of available culture, sport and health facilities. Although, the objectives of the inhabitants and tourists are very different, their basic structural needs and the underlying methodology have common characteristics. In this prospective, the central element is the ability to build networks that connect the nodes of interest, which are functional (services at various levels), cultural (historical and artistic emerging features), and leisure (dedicated sport facilities and locations). Furthermore, the paper investigates the paths and times of networks connections, providing particular attention to multipurpose trips consistence of either dwellers or tourists.